Catalytic oxidative/extractive desulfurization of model and untreated diesel using hybrid based zinc-substituted polyoxometalates - Ribeiro, Susana O. (2016)
The desulfurization efficiency of various hybrid zinc-substituted polyoxometalates ([PW11Zn(H2O)O39]5−, abbreviated as PW11Zn) was here investigated for the first time and optimized using sustainable systems conciliating successfully the liquid–liquid extraction and the oxidative catalytic process. Initially, the desulfurization studies were performed using a model diesel containing a mixture of the most refractory sulfur compounds and later extended to an untreated real diesel. In both cases, acetonitrile was used as extraction solvent and aqueous H2O2 as oxidant. High level of desulfurization was achieved using model and untreated diesels after few hours. The quaternary ammonium catalysts (TBAPW11Zn and ODAPW11Zn) showed higher catalytic desulfurization efficiency than the ionic liquid catalyst (BMIPW11Zn). The TBAPW11Zn behaved as a homogeneous catalyst immobilized in the extraction solvent, while the ODAPW11Zn with the long carbon chain behaved as a heterogeneous catalyst capable to be recovered from the system. Both quaternary ammonium catalysts showed to be successfully reused/recycled for various consecutive desulfurization cycles.